p-Nitrophenol UDP-Glucuronosyltransferase Activity in Liver Microsome from Sprague Dawley Rats Fed with Methanol Extract of Orthosiphon stamineus (Misai Kucing) - J.H, Chin; S, Ismail; A.H, Hussin; (Zhari Ismail), Ismail Z. (Malaysian Journal of Science, 2005)
This in-vivo (acute) study involved the use of twenty five normal old male Sprague Dawley rats (>52 weeks) weighing 350Ã‚Â±50 g and each group (n=5) administered orally with a single dose of methanol extract of Orthosiphon stamineus (Misai Kucing) ranging from 5 mg/kg, 31.25 mg/kg, 125 mg/kg to 500 mg/kg. Controls were treated with the respective vehicles through the same route under similar conditions. After 24 hour of dose administration, rats were sacrificed. Microsomes were prepared by calcium precipitation method [1] and used for UDP-glucuronosyltransferase (UGT) activity study towards p-nitrophenol (pNP). The protein levels of microsomes were measured by the method of Lowry et al [2]. Results were expressed as nmol/min/mg protein and analyzed by Dunnett Test. The results showed that methanol extract of Misai Kucing increases pNP UGT activity significantly especially at 31.25 mg/kg (P<0.01), 125 mg/kg (P<0.01) and 500 mg/kg (P<0.01).